Genetic characterization of chicken infectious anaemia viruses isolated in Korea and their pathogenicity in chicks - Song, HyeSoon; Kim, HyeonSu; Kwon, YongKuk; Kim, HyeRyoung (Frontiers in Cellular and Infection Microbiology, 2024)
Chicken infectious anaemia virus (CIAV) causes severe anemia and immunosuppression through horizontal or vertical transmission in young chickens. Especially, vertical transmission of virus through the egg can lead to significantly economic losses due to the increased mortality in the broiler industry. Here, 28 CIAV complete sequences circulating in Korea were first characterized using the newly designed primers. Phylogenetic analysis based on the complete sequences revealed that CIAV isolates were divided into four groups, IIa (2/28, 7.1%), IIb (9/28, 32.1%), IIIa (8/28, 28.6%) and IIIb (9/28, 32.1%), and exhibited a close relationship to each other. The major groups were IIb, IIIa and IIIb, and no strains were clustered with a vaccine strain available in Korea. Also, for viral titration, we newly developed a quantitative PCR assay that is highly sensitive, reliable and simple. To investigate the pathogenicity of three major genotypes, 18R001(IIb), 08AQ017A(IIIa), and 17AD008(IIIb) isolates were challenged into one-day-old specific-pathogen-free (SPF) chicks. Each CIAV strain caused anaemia, severe growth retardation and immunosuppression in chickens regardless of CIAV genotypes. Notably, a 17AD008 strain showed stable cellular adaptability and higher virus titer in vitro as well as higher pathogenicity in vivo. Taken together, our study provides valuable information to understand molecular characterization, genetic diversity and pathogenicity of CIAV to improve management and control of CIA in poultry farm.